The Psychosocial Process of College Dropout: The CEGEP Experience - Rivière, Bernard (Canadian Journal of Counselling and Psychotherapy, 2007)
The results of this qualitative, descriptive, and exploratory research present a psychosocial process of dropping out at the college level. This process is analyzed through three periods (pre-dropout, dropout and post-dropout) comprising eight regressive steps induced by mutual maladaptation between the student and the CEGEP. However, the post-dropout period is a moratorium during which integration and self-reactualization take place.